Analysis of Heat Transfer in the Process of Smelting Plastic Waste in the Form of Paving Blocks - Maulani, Irna Sari; Syamsuri, Heris (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2023)
Plastic waste is an inseparable part of human life. People's habit of burning accumulated plastic waste can release heavy metal content in plastic and toxic chemicals such as dioxins which can interfere with the respiratory process. There is another way to reduce plastic waste, namely by melting plastic waste into paving blocks. The process of melting plastic waste is carried out in a melting furnace. The purpose of this study is to analyze the heat transfer that occurs in the smelting furnace. The method used in this research is heat transfer analysis using FEM analysis and heat transfer analysis through experimental studies. The results obtained in the FEM analysis, the heat generated by the smelting furnace ranges from 212-300 ⁰C. While the heat generated in the measurement process is 280 ⁰C. Analysis of heat transfer that occurs in the smelting furnace obtained a figure of 1.95 Watt. The value of the wasted heat from the smelting furnace is 6.77 W. This means that the wasted heat is greater than the heat generated from the smelting furnace, this will result in a waste of energy. To overcome wasted heat, it is recommended to add insulating material to the furnace around smelting.